2018
DOI: 10.1186/s13018-018-0787-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of calcium pyrophosphate dihydrate crystals in knee meniscus by dual-energy computed tomography

Abstract: BackgroundCalcium pyrophosphate dihydrate (CPPD) crystals are commonly observed in osteoarthritic joints. The aim of our study was to investigate the efficacy of a dual-energy computed tomography (DECT) for detecting CPPD crystals in knee meniscus.MethodsTwenty-six patients undergoing primary total knee arthroplasty were included in the study. Radiographs of knee joint and synovial fluid specimens were analyzed for the presence of CPPD crystals. Meniscus extracted during surgery was scanned using DECT. Sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 30 publications
(35 reference statements)
0
24
0
2
Order By: Relevance
“…Other imaging modalities such as ultrasound and dual‐energy computed tomography (DECT) are being increasingly used to aid in the diagnosis of gout (). A recent study showed that DECT can also detect CPP crystal deposits ex vivo, with a reported sensitivity and specificity of 78% and 94%, respectively (). However, the role of these imaging techniques in other crystal deposition diseases is less well defined, and they cannot easily distinguish between different calcium crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging modalities such as ultrasound and dual‐energy computed tomography (DECT) are being increasingly used to aid in the diagnosis of gout (). A recent study showed that DECT can also detect CPP crystal deposits ex vivo, with a reported sensitivity and specificity of 78% and 94%, respectively (). However, the role of these imaging techniques in other crystal deposition diseases is less well defined, and they cannot easily distinguish between different calcium crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Так, в проводимых до настоящего времени популяционных исследованиях в качестве основного классификационного критерия использовались рентгенологические признаки ХК лучезапястных суставов, который, во-первых, не тождествен БДПК, а во-вторых, имеет довольно низкую чувствительность [0,29; 95% доверительный интервал (ДИ) 0,05-0,62] и специфичность (0,20; 95% ДИ 0,15-0,55) [13]. В целом чувствительность рентгенологически выявляемого ХК составляет примерно 40%, если брать в качестве эталона наличие кристаллов ПФК в СЖ [13][14][15][16]. Как следствие, эта оценка весьма приблизительна, поскольку 25-50% пациентов, у которых в СЖ выявляются кристаллы ПФК, не имеют рентгеновских признаков ХК коленных суставов [17].…”
Section: Discussionunclassified
“…I read with interest the article by Tanikawa et al [ 1 ] that appeared recently in the Journal of Orthopedics Surgery Research. Greatly, this is an interesting paper about the role of dual-energy computed tomography (DECT) in the detection of chondrocalcinosis.…”
Section: To the Editormentioning
confidence: 99%
“…Tanikawa et al [ 1 ], however, did not mention in their article about the availability of ultrasound and the possibility to scan several joints with lower expenditures at the same visit. On the other hand, while this paper has appeared, mounts of publications demonstrate that ultrasound is an excellent modality in the diagnosis of chondrocalcinosis.…”
Section: To the Editormentioning
confidence: 99%